Topic change in casual conversation : an exploratory study - Andreau, Laura Elena; Morales, Marcela; Moyano, Sara (2010)
This study is part of the Cohesion and Coherence in Casual Conversation research project (UNLP), which aims to contribute to the description of casual conversation, drawing on a range of approaches to provide a theoretical framework that can help explain the complexities of informal talk. When speakers engage in casual conversation, they do not have a prescribed topic agenda to follow. Given the symmetrical nature of the relation among participants, speakers are free to change, shift, drift, digress or resume topics (Stenström, 1994). The focus of this study is on topic change and topic shift and some of the strategies employed by speakers to introduce a new topic or move away from the current one. Our data consists of 15 dialogues drawn from the ECAr (Español Coloquial de Argentina) corpus, a collection of 52 informal conversations recorded between 2000 and 2010, involving male and female university students who know each other prior to the recordings. Results obtained by means of qualitative analysis show that speakers make different Mood choices (Halliday & Matthiessen, 2004) often employing a range of markers to change or shift topic which belong either in the textual or interpersonal theme (Eggins, 2004).